The influence of brand experience on brand equity: the mediating role of brand love in a retail fashion brand - Ferreira, Pedro (2022)
Based on a retail fashion brand, this article investigates how brand experience affects brand equity when it is mediated by brand love. Actual consumers are well-informed, demanding, and prefer brands that can surprise them over time. As such, offering emotional signals, meaning development, and strategic planning are critical to success when it comes to building strong and enduring relationships with customers. Based on 560 responses to a survey conducted in-store, this study tests the influence of brand experience on overall brand equity, through brand love, using a model of structural equations. The findings imply that brand experience dimensions play a different role in eliciting emotional reactions, such as brand love, which helps to reinforce brand equity. Re- search on the paths to consumer-based brand equity in the retail environment is still scarce. Explor- ing this pathway using the customer-brand relationship theory and integrating brand experience and brand love has fascinating potential, but it is still unexplored. Finally, another strength of this research is the test of brand experience dimensions (sensory, intellectual, affective, and behavioral), thus offering more operational insights for theory and practice. The results are based on the study of one brand in one specific country, which limits generalizations. Managers should pay special atten- tion to the emotional impulses provided by a brand to its customers. Building on these triggers via experiences strengthens strong emotional reactions like brand love, which contributes to brand equity.